Soap and water cleaning versus bleach-based cleaners for eliminating SARS-CoV-2 infection - Ekong E. Udoh; Ubong A. Udoh; Abiodun Egwuenu; Ekpereonne B. Esu; Aruk Eteng; Faithman E. Ovat; Uduak Okomo; Olabisi Oduwole; Joseph Okebe; Martin Meremikwu (Journal of Public Health in Africa)
Background: Households and community settings are important hubs for the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As understanding of viral transmission improves, infection prevention and control (IPC) policies need to be updated.